Admissibility of Anonymous Witness Testimony in Evidence: Foreign Experience (International Journal of Scientific Trends, 2026)
This article examines the admissibility of anonymous witness testimony in criminal proceedings on the basis of foreign legal experience and international judicial practice. It explores the reasons for introducing the institution of anonymous witnesses, its role in ensuring witness security, and its impact on the accused’s right to defence and the principle of a fair trial. Drawing on the jurisprudence of the European Court of Human Rights, international criminal tribunals, and the laws of selected foreign jurisdictions, the study comparatively analyses the criteria for admitting anonymous witness testimony, the limits of its evidentiary value, and the procedural safeguards that must accompany its use. The article argues that it is inappropriate both to categorically prohibit anonymous witness testimony and to normalize it as an ordinary form of evidence. The findings demonstrate that such testimony may be considered admissible only in exceptional circumstances, where a real threat exists, where the requirements of necessity and proportionality are satisfied, and where adequate procedural mechanisms compensate for the limitations imposed on the defence.